2022
DOI: 10.1007/s11356-022-22886-0
|View full text |Cite
|
Sign up to set email alerts
|

Can green finance promote urban green development? Evidence from green finance reform and innovation pilot zone in China

Abstract: This study aims to evaluate the effect of the green finance reform and innovation pilot zone (GFPZ) policy on urban green development. Based on city-level panel data in China from 2012 to 2019, a difference-in-differences model was employed to examine the effects of China’s GFPZ policy on the city’s green total factor productivity (GTFP). Results show that (1) the GFPZ policy has promoted the GTFP of pilot cities, a conclusion that still holds after performing multiple robustness tests. (2) Compared to non-pil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 72 publications
0
25
0
Order By: Relevance
“…Additionally, in 2017, China created green finance reform and innovation pilot zones (GFPZ) in six provinces and energy consumption rights trading (ECRT) pilot zones in four provinces. The effects of LCCP, CEPT, BCPP, GFPZ, and ECRT on energy have been proven [49][50][51][52][53]. Only the impact of the NEDC policy is considered in column (1), while the other columns of Table 5 show the regression results after including LCCP, CETP, BCPP, GFPZ, and ECRT, respectively.…”
Section: Excluding the Influence Of Other Policiesmentioning
confidence: 99%
“…Additionally, in 2017, China created green finance reform and innovation pilot zones (GFPZ) in six provinces and energy consumption rights trading (ECRT) pilot zones in four provinces. The effects of LCCP, CEPT, BCPP, GFPZ, and ECRT on energy have been proven [49][50][51][52][53]. Only the impact of the NEDC policy is considered in column (1), while the other columns of Table 5 show the regression results after including LCCP, CETP, BCPP, GFPZ, and ECRT, respectively.…”
Section: Excluding the Influence Of Other Policiesmentioning
confidence: 99%
“…A dynamic spatial Durbin model has confirmed that green finance in China is efficient and can lower carbon dioxide emissions. Zhang et al (2022) attempted to determine how green finance enhanced urban citylevel green development in China from 2002 to 2019. The major results highlighted the role of green finance in lowering urban energy intensity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At present, most of the research on green development in academia focuses on horizontal measurement and impact factors. The first method of measuring green development is to establish an input-output indicator system and use the data envelope analysis (DEA) method to measure total factor productivity to characterise urban green development [19][20][21]. The second is to adopt a comprehensive indicator evaluation system, using the entropy method to measure comprehensive indicators to characterise urban green development [22][23][24].…”
Section: Literature Reviewmentioning
confidence: 99%